Efficacy and safety of novel anticoagulants versus vitamin K antagonists in patients with mild and moderate to severe renal insufficiency: Focus on apixaban. (15th December 2016) - Pelliccia, Francesco; Rosanio, Salvatore; Marazzi, Giuseppe; Poggi, Sara; Tanzilli, Alessandra; Greco, Cesare; Gaudio, Carlo; Rosano, Giuseppe
Abstract: The high risk of both stroke and major bleeding in atrial fibrillation (AF) patients with chronic kidney disease (CKD) defines an important population for whom the assessment of the balance between the risk of ischemic stroke and of bleeding is essential. The use of novel oral anticoagulants (NOACs) may be a viable option in this population due to their greater net clinical benefit than warfarin, as demonstrated by the results of the clinical phase III trials. NOACs have been found to have a greater net clinical benefit than warfarin in patients at high risk of either stroke (CHADS2 ≥ 1 or CHA2DS2-VASc score ≥ 2) or bleeding (HAS-BLED ≥ 3). Noteworthy, it has been found also a positive net clinical benefit with apixaban and dabigatran 110 mg BID in patients with CHADS2 score = 0 and HAS-BLED score ≥ 3. At CHA2DS2-VASc score = 1, apixaban and both doses of dabigatran were superior to warfarin in terms of the net clinical benefit. Available scientific evidence might help in clinical decision-making regarding the use of NOACs in patients with CKD who are at high risk for both stroke and bleeding. Overall, current findings provide a rationale for the choice of apixaban or rivaroxaban over dabigatran in patients with AF and stage III CKD. Out of the NOACs, only apixaban has been recently approved for the use in patients with end-stage renal dysfunction on hemodialysis (the recommended dose of 5 mg twice daily should be halved in patients with body weight of ≤ 60 kg and or age ≥ 80 years). Highlights: Patients with atrial fibrillation (AF) and chronic kidney disease (CKD) are at risk of ischemic stroke and bleeding NOACs have a greater net clinical benefit than warfarin in patients at risk of either stroke or bleeding Scientific evidence help in clinical decision-making on the use of NOACs in patients with CKD Currently, only apixaban has been approved for the use in patients with end-stage renal dysfunction on hemodialysis